Aplikasi Monitoring Pegawai ASN Kelurahan Pademangan Timur - Rafih, Muhammad; Malabay (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This study aims to design, develop, and test an Android-based monitoring application for CivilServants (ASN) in Kelurahan Pademangan Timur using the prototypemethod. The background ofthe study highlights the need for an effective system for managing ASN performance at the villagelevel and the lack of research focusing on similar applications at this level. The problemidentification points to the absence of an integrated system, limited information accessibility, lackof transparency, insufficient use of information technology, and gaps in previous research. Thisstudy produces an application that enables effective monitoring and management of ASNperformance, with benefits such as increased efficiency, transparency, user satisfaction, andcontributions to the development of information technology in the public sector. The results of thisstudy are expected to provide a reference for the development of similar applications in otherregions of Indonesia.